SAT0038 Osteoclasts Activate Chondrocyte Catabolism Through S1P Production. (9th June 2015) - Cherifi, C.; Ea, H.-K.; Funck-Brentano, T.; Hay, E.; Cohen-Solal, M.
Abstract : Background: Subchondral bone features accompanied all stages development of osteoarthritis (OA). We have previously demonstrated that high osteoclastogenesis and bone remodeling is observed at the initiation of OA, while inhibition of osteoclast function prevents bone and cartilage catabolism in murine OA models. Objectives: Our purpose was to evaluate how osteoclast-derived factors affect the chondrocyte metabolism and to further investigated the role of S1P, an osteoclast-secreted molecule in chondrocyte metabolism and osteoarthritis. Methods: Primary murine chondrocytes were cultured with conditioned medium of osteoclasts (Oc-M) or RAW cells (Raw-CM) to analyze the expression of catabolism and anabolism genes (RT-qPCR). Femoral head explants were cultured in the presence of Oc-CM for 48h to quantify matrix protein expression and proteoglycan content and further investigated the role of S1P released in Oc-CM in the presence of JTE-013, a S1P receptor S1PR2 antagonist. Results: Oc-CM reduced the proteoglycan release in primary chondrocytes and activated p38MAPkinase pathway. Increased expression of catabolic enzymes (MMP-3, -13, Adamts-4, -5) was observed only with Oc-CM while reduction of expression of anabolic markers (Col2, ACAN, Sox9) was induced with both Oc-CM and Raw-CM. Oc-CM increased the chondrocytic expression of S1P receptors 1 to 4 and the inhibition of S1PR2 protected chondrocytes from degradation enzymes induced by Oc-CM. In joint explants, JTE-013 reversed proteoglycan loss and NITEGE expression induced by Oc-CM, and reduced proteoglycan release and expression of MMP-3/MMP-13 by the chondrocytes. Our results indicate that S1P produced in Oc-CM promotes chondrocyte catabolism. Conclusions: These data demonstrated that osteoclast-secreted factors disrupt the balance of chondrocyte metabolism through the production of S1P. Therefore, subchondral bone manipulation may affect chondrocyte function and OA. Disclosure of Interest: None declared